A study of dysmenorrhea during menstruation in adolescent girls - Agarwal Anil; Agarwal Anju (Wolters Kluwer Medknow Publications, 2010)
Research question: What is the prevalence of dysmenorrhea severity and its associated symptoms among adolescent girls? Objectives: (1) To study the prevalence of dysmenorrhea in high school adolescent girls of Gwalior. (2) To study the evidence of severity of the problem with associated symptoms and general health status. Study design: An explorative survey technique with a correlational approach. Setting and Participants: Nine hundred and seventy adolescent girls of age 15 to 20 years, studying in the higher secondary schools (Pre-University Colleges) of Gwalior. Statistical analysis: Percentages, Chi-square test, and Test-Retest Method. Results: The prevalence of dysmenorrhea in adolescent girls was found to be 79.67%. Most of them, 37.96%, suffered regularly from dysmenorrhea severity. The three most common symptoms present on both days, that is,day before and first day of menstruation were lethargy and tiredness (first), depression (second) and inability to concentrate in work (third), whereas the ranking of these symptoms on the day after the stoppage of menstruation showed depression as the first common symptoms. Negative correlation had found between dysmenorrhea and the General Health Status as measured by the Body surface area.